Effect of particle size on the kinetics of filtration dolomite - Escajadillo, Dante (2012)
Filtration is an important unit operation for mineral processing in the concentrator plants and important study its phenomenology and behavior of the variables and parameters involved. Filtration tests were carried out with powdered dolomite, natural monotamaños different size distribution. Filtration rate with time was determined, and the filtration rate T / Vf was calculated vs. Vf, which was obtained from the slope and the intercept on the ordinate and then calculate the kinetic model of filtration for each monotamaños well as in the natural distribution.